Determining Near‐Bottom Fluxes of Passive Tracers in Aquatic Environments. Issue 6 (23rd March 2018) - Bluteau, Cynthia E.; Ivey, Gregory N.; Donis, Daphne; McGinnis, Daniel F.
Abstract: In aquatic systems, the eddy correlation method (ECM) provides vertical flux measurements near the sediment‐water interface. The ECM independently measures the turbulent vertical velocities w ′ and the turbulent tracer concentration c ′ at a high sampling rate (> 1 Hz) to obtain the vertical flux w ′ c ′ ¯ from their time‐averaged covariance. This method requires identifying and resolving all the flow‐dependent time (and length) scales contributing to w ′ c ′ ¯ . With increasingly energetic flows, we demonstrate that the ECM's current technology precludes resolving the smallest flux‐contributing scales. To avoid these difficulties, we show that for passive tracers such as dissolved oxygen, w ′ c ′ ¯ can be measured from estimates of two scalar quantities: the rate of turbulent kinetic energy dissipation ε and the rate of tracer variance dissipation χ c . Applying this approach to both laboratory and field observations demonstrates that w ′ c ′ ¯ is well resolved by the new method and can provide flux estimates in more energetic flows where the ECM cannot be used. Key Points: We derive a relationship to predict turbulent vertical fluxes of passive tracers in the log layer The estimated fluxes from this relationship agreed well with those obtained directly with the typically applied eddy correlation method Turbulent fluxes can be estimated in more energetic flows and/or more tracers than previously possible